2022
DOI: 10.3390/e24101436
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Theory and Memory Effects of Homogeneous Inelastic Granular Gases under Nonlinear Drag

Abstract: We study a dilute granular gas immersed in a thermal bath made of smaller particles with masses not much smaller than the granular ones in this work. Granular particles are assumed to have inelastic and hard interactions, losing energy in collisions as accounted by a constant coefficient of normal restitution. The interaction with the thermal bath is modeled by a nonlinear drag force plus a white-noise stochastic force. The kinetic theory for this system is described by an Enskog–Fokker–Planck equation for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…The thermal and entropic approaches to the Mpemba effect have been scarcely compared [62,90]. In ref.…”
Section: T Ib < T Ia and Excess Kurtosis A Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal and entropic approaches to the Mpemba effect have been scarcely compared [62,90]. In ref.…”
Section: T Ib < T Ia and Excess Kurtosis A Bmentioning
confidence: 99%
“…In ref. [90], it was shown that the thermal Mpemba effect may appear without its entropic counterpart -or vice versain a molecular fluid with non-linear drag. Therein, some situations appear in which the kinetic temperature overshoots the stationary value, which makes it necessary to revise the usual definition of the thermal Mpemba effect in this scenario.…”
Section: T Ib < T Ia and Excess Kurtosis A Bmentioning
confidence: 99%
See 1 more Smart Citation
“…After a year-long preparation and a rigorous peer-review process, 12 articles were finally accepted for publication in this Special Issue. These articles report the latest developments in kinetic-theory-related numerical schemes [1,2] and typical applications in multiphase flows [3], thermal flows [4], micro/nano flows [5,6], flows in porous media [7], and compressible flows [8,9], as well as other areas of fluid dynamics [10][11][12]. Specifically, Song et al [1] proposed a simplified linearized Boltzmann method for the effective simulation of acoustic propagation with a lower cost of virtual memory.…”
mentioning
confidence: 99%
“…Morozov and Titarev [10] utilized three numerical tools to study the dynamics of gas expansion due to intense nanosecond laser evaporation into vacuum, with specific attention paid to factors that are essential for experimental measurements. Megías and Santos [11] established a numerical model to interpret interactions between the dilute granular gases and a thermal bath made from smaller particles, and found that the Sonine approximation performs better than the Maxwellian approximation in revealing inelasticity, drag nonlinearity and memory effects. Qi et al [12] employed an immersed boundary-lattice Boltzmann method to simulate self-propelled particles in a simple shear flow, and studied the effects of multiple flow parameters (swimming Reynolds number, flow Reynolds number and blocking rate) on the kinematics and flow patterns.…”
mentioning
confidence: 99%